2006
DOI: 10.1111/j.1748-5967.2006.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the silk apparatus of the comb‐footed spider, Achaearanea tepidariorum (Araneae: Theridiidae)

Abstract: The microstructural organization of the silk‐spinning apparatus of the comb‐footed spider, Achaearanea tepidariorum, was observed by using a field emission scanning electron microscope. The silk glands of the spider were classified into six groups: ampullate, tubuliform, flagelliform, aggregate, aciniform and pyriform glands. Among these, three types of silk glands, the ampullate, pyriform and aciniform glands, occur only in female spiders. One (adult) or two (subadult) pairs of major ampullate glands send sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In O. striatipes , the ampullate spigots are located on both the anterior and the posterior spinnerets, and the total four pairs of ampullate spigots send secretory ductules to both the anterior and the median spinnerets. This arrangement of the ampullate spigot has been commonly reported in most araneid spiders except for a peculiar modification in Theridiidae spiders (Moon & An 2006). It has also been reported that the two kinds of ampullate gland (major and minor) in araneid spiders produce different types of silk material (Tillinghast & Christenson 1984; Tillinghast & Townley 1986, 1987).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In O. striatipes , the ampullate spigots are located on both the anterior and the posterior spinnerets, and the total four pairs of ampullate spigots send secretory ductules to both the anterior and the median spinnerets. This arrangement of the ampullate spigot has been commonly reported in most araneid spiders except for a peculiar modification in Theridiidae spiders (Moon & An 2006). It has also been reported that the two kinds of ampullate gland (major and minor) in araneid spiders produce different types of silk material (Tillinghast & Christenson 1984; Tillinghast & Townley 1986, 1987).…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have found that divergence of spider species correlates with evolution of the ampullate gland (Foelix 1996), and it has also been shown that selection and molecular events resulted in the evolution of the ampullate silk proteins (Craig & Riekel 2002). Like other araneid spiders, such as wandering spiders (Moon 1998; Moon & An 2005) and other web‐building spiders (Tillinghast & Townley 1986; Peters & Kovoor 1991; Moon 2002; Park & Moon 2002; Moon & Tillinghast 2004; Moon & An 2006), the ampullate glands were the largest silk glands observed in O. striatipes and were used for making draglines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of Cupiennius and Achaearanea adult female silk glands. Differences between the glands of these species and glandular differences between spinnerets within one animal from our own and previous observations (87,100) are illustrated. Different gland types are distinguished on morphological and histochemical grounds, i.e.…”
Section: Discussionmentioning
confidence: 93%
“…To test the possibility that the pyriform fibres in the scaffolding and gumfoot discs could be chemically different, we cite the work of Moon et al 9 that shows that female A. tepidariorum spiders possess 90-100 pairs (total 180-200) of pyriform glands that feed into discrete pyriform spigots on the anterior spinnerets. The total number of pyriform spigots is consistent with the total number of fibres measured by us in the gumfoot discs (188 ± 20).…”
Section: Effect Of Architecture On Adhesionmentioning
confidence: 99%